Experience with olokizumab in the treatment of polymyalgia rheumatica and giant cell arteritis: A series of cases - Alexey D. Meshkov; Alexey L. Maslyansky; Nikolay M. Bulanov; Ekaterina E. Filatova; Pavel I. Novikov; Anton V. Naumov; Olga N. Tkacheva (Научно-практическая ревматология, 2024)
Glucocorticoids are the basis for the treatment of giant cell arteritis (GCA) and polymyalgia rheumatica (PMR), however, their long-term use is associated with a number of well-known side effects. Despite the fact that a significant number of patients with these diseases require long-term treatment, approaches to long-term therapy remain insufficiently developed. The role of traditional anti-inflammatory drugs remains uncertain due to insufficient efficacy and inconclusive evidence base. A possible solution of this problem is the use of biological agents, in particular, affecting the interleukin (IL-6) axis. This series of clinical observations presents the experience of using the IL-6 inhibitor olokizumab in the treatment of GCA and PMR. The data obtained are consistent with the positive international experience of using drugs of this group and demonstrate both efficiency of disease activity control and a pronounced steroid-sparring effect. Olokizumab is a promising drug for the treatment of GCA and PMR.